Development of E-Modules Integrate with PBL (Problem Base Learning) in High School Physicts Subject Class XI - Nurhasnah Sikumbang; Jasrial; Ridwan; Rayendra (Postgraduate, University of Mataram, 2025)
This study aims to test the feasibility, practicality and effectiveness of the development of e-modules based on Problem Based Learning (PBL) on sound wave material in Physics class XI at SMA Pertiwi 1 Padang. The method used in this research is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate). The sample used in this study was class XI students at SMA Pertiwi 1 Padang totaling 33 students. The instrument used in the study was a questionnaire sheet for validation of feasibility and practicality. Data collection techniques in this study include tests in the form of pre-test and post-test work while non-tests include observation, questionnaire filling, interviews and documentation. The results showed that the feasibility value of developing e-modules with PBL syntax provided by media, material and language experts met the criteria with an average validity of 82.53%, 88.51%, and 100% respectively (very valid category). The practicality test by students showed an average practicality level of 93.87% (very practical category). Based on the results of the pre-test and post-test, the development of e-modules with PBL syntax meets the effective criteria, this can be seen from the effectiveness analyzed with the results of a significant increase based on the t test (t_hitung = 5.51 > t_table = 2.037). Thus, this PBL-integrated e-module is declared valid, practical, and effective as Physics learning media, and is able to significantly improve students' concept understanding of sound waves material.